The Unmet Needs in Atopic Dermatitis Control in Latin America: A Multidisciplinary Expert Perspective (2021)
ABSTRACT: Introduction: Adoption of control tools for atopic dermatitis (AD) in Latin America (LA) is currently very limited. Clinical assessment tools represent a practical method to measure the impact of treatment on disease activity and on the quality of life of patients. However, the use of these tools in the LA clinical practice setting is limited. Methods: A selected panel of Latin American experts in fields related to atopic dermatitis were provided with a series of relevant questions to address prior to the multi-day conference. Within this conference, each narrative was discussed and edited by the entire group, through numerous drafts and rounds of discussion, until a consensus was achieved. Results: The panel proposes specific and realistic recommendations for implementing control tools for AD care in LA. In creating these recommendations, the authors strove to address all barriers to the widespread use of these tools. Conclusion: This article includes a narrative analysis of barriers to AD control in LA and provides necessary recommendations to integrate and increase the use of validated AD control assessment tools throughout the region.